Ethnographie de deux restitutions manquées - Mariangela Roselli (Revue d'anthropologie des connaissances)
The papers deals with the problems of non-reception as form of resistance. On the occasion of two inquiries of ground led in two libraries between 2006 and 2008, techniques of oral restitution and debate of results are set up around a committee of piloting. After a very favourable reception of the researcher during several months (participation at the different levels of tasks, at the meetings of teams and services, direct observations and individual discussions), the report of inquiry, sent under electronic format by direction, is ignored in the first site. In the second site, the restitution by a Power Point diaporama is questioned by the wage earners claiming more dialogic and more informal forms of exchange. Taking support on these two experiments, the paper describes both situations and analyses conflicts and stakes that can emerge when using electronic and graphic tools.